2018
DOI: 10.1152/japplphysiol.01132.2017
|View full text |Cite
|
Sign up to set email alerts
|

Protein intake in the early recovery period after exhaustive exercise improves performance the following day

Abstract: TT and sprint performances were improved 18 h after exhaustive cycling by CHO-PROT supplementation during the first two hours of recovery compared with isoenergetic CHO supplementation. Our results indicate that intake of carbohydrate plus protein after exhaustive endurance exercise more rapidly converts the body from a catabolic to an anabolic state than carbohydrate alone, thus speeding recovery and improving subsequent cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(70 citation statements)
references
References 64 publications
(89 reference statements)
8
54
2
Order By: Relevance
“…There is a considerable volume of research, which has investigated a wide variety of protein ingestion strategies for the promotion of training adaptations and recovery from damaging exercise [84]. Therefore, in the absence of studies which have directly used soccer as an exercise model, much of the recommendations are based on work examining other participant populations and exercise protocols [32,74,105].…”
Section: Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a considerable volume of research, which has investigated a wide variety of protein ingestion strategies for the promotion of training adaptations and recovery from damaging exercise [84]. Therefore, in the absence of studies which have directly used soccer as an exercise model, much of the recommendations are based on work examining other participant populations and exercise protocols [32,74,105].…”
Section: Proteinmentioning
confidence: 99%
“…The co-ingestion of milk-based protein and CHO has previously been shown to reduce blood myoglobin, creatine kinase, and increase peak muscle torque 48 h after a damaging exercise bout, compared to CHO alone [32]. More recently, Sollie et al [105] also demonstrated that CHO and protein co-ingestion (0.8 and 0.4 g/kg/h, respectively) was more effective at promoting anabolism compared to the ingestion of 1.2 g/kg/h CHO following exhaustive aerobic exercise. Furthermore, the CHO and protein strategy also improved sprint performance by 3.7% and time trial performance by 8.5%, 18 h after the exhaustive exercise bout.…”
Section: Post-match Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using exhaustive exercise and short recovery periods ranging from ∼4 to 18 h have implied a role of amino acid repletion in the recovery phase for subsequent performance (Williams et al, 2003;Rustad et al, 2016;Sollie et al, 2018;Dahl et al, 2020), although there is still some debate on the effectiveness of protein supplementation for recovery and performance in endurance exercise (Kloby Nielsen et al, 2020). SAA metabolism and availability may be implicated in these processes through several important mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate is the main energy substrate during exercise at intensities ~75% of maximal oxygen uptake (Hermansen, Hultman, & Saltin, 1967;Romijn et al, 1993;Rustad et al, 2016;Sollie et al, 2018), and prolonged training at such intensities improves glucose tolerance. Moreover, exercise at such intensity effectively improves skeletal muscle oxidative capacity and expression of many proteins involved in glucose uptake.…”
Section: Introductionmentioning
confidence: 99%